1996
DOI: 10.1007/bf00335561
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of tolerance to rat hepatic allografts by spleen-derived passenger leukocytes

Abstract: The tolerance induced by orthotopic liver transplantation (OLT) in certain combinations of rat strains can be prevented by total body irradiation (TBI) of the donor. We demonstrate here that the intravenous inoculation of splenic leukocytes into irradiated donors before OLT could re-establish tolerance in association with a state of microchimerism detected in the recipients. When donor DA (RT1a) strain rats were irradiated with 1000 rad 24 h before liver harvesting and subsequent liver implantation into PVG re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
5
18
1
Order By: Relevance
“…However, TBI (1000 rads) of DA donor rats 24 h prior to OLT prevented the induction of tolerance in PVG recipients [26], as shown in our group 3 (Table 1). Group 2 showed that graft viability was not affected by irradiation.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…However, TBI (1000 rads) of DA donor rats 24 h prior to OLT prevented the induction of tolerance in PVG recipients [26], as shown in our group 3 (Table 1). Group 2 showed that graft viability was not affected by irradiation.…”
Section: Resultssupporting
confidence: 71%
“…Using a naturally tolerogenic combination of rats in OLT, we have demonstrated, as have others [29], that TBI of the donor fails to induce tolerance in these recipients. However, unlike other studies using parking of the liver [27, 291, reconstitution of the irradiated donor with bone marrow cells [31], or injection of cells into the recipient, we reestablished liver-induced tolerance simply by injecting naive donor type spleen cells into the irradiated donor 24 h prior to transplantation [26]. Furthermore, our present study shows that splenic "T-cell-enriched" populations may play an important role in the restoration of liver graft acceptance, although we should further investigate the involvement of radio-resistant dendritic cells [8,29] or intrahepatic hematopoietic stem cells [2,20] in the induction of tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore may well be possible that a specific number of donor leucocytes is required to migrate to a given recipient organ for tolerance to be achieved. Indirect evidence to support this contention has recently been reported by Shimizu et al [17]. The investigators in this study have shown that if a PVG recipient that has been transplanted with an irradiated DA liver received 1 : 5 × 10 8 DA splenocytes following OLT then tolerance is maintained.…”
Section: Discussionsupporting
confidence: 56%
“…This transplant phenomenon has been described in some detail, and is observed following both clinical transplantation [1][2][3][4][5][6][7][8][9] and in experimental animal models [10][11][12][13][14][15][16][17]. It has also been shown to occur regardless of whether immunosuppressive drugs are used as in the clinical situation [1][2][3][4][5][6][7][8][9] and in the absence of immunosuppression, as is the case for some animal models involving liver transplantation [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation